URGENSI HUKUM PADA PENDERITA KELAINAN SEKSUAL (BDSM DAN HOMOSEKSUAL) - atiqah balqis, Ainun agustina (jurnal.unprimdn.ac.id, 2024)
Sufferers of BDSM and homosexual mental disorders are at great risk of being involved in criminal acts, but there is no law that specifically regulates criminal acts committed from BDSM and homosexual activities. The aim of this research is to determine the extent of legal urgency required for perpetrators of criminal acts who have sexual disorders which are included in mental disorders because Article 44 of the Criminal Code only regulates reasons for forgiveness for ODGJ. This research uses qualitative research methods and a descriptive approach and uses normative data collection techniques. The results of the research obtained are that there are no monetary crime laws regulating sexual disorders, especially BDSM, however, the crime of sodomy can be charged under the obscenity article of the Criminal Code and the Child Protection Law. Perpetrators of criminal acts who have sexual disorders are also subject to law because they do not fulfill the elements stated in Article 44 of the Criminal Code.